Strategic IS/IT Planning for Enhanced Competitiveness and Operational Efficiency at PT. Songgo Jati Baru: Applying the Ward and Peppard Method - Firmansya, Andika Jati; Amelia, Putri (Journal of Information System and Informatics, 2025)
This study designs an integrated IS/IT strategy to enhance PT. Songgo Jati Baru's operational efficiency and global competitiveness in the trading and services sector. A qualitative approach was employed, utilizing data collection methods such as focus group discussions, document analysis, observation, and interviews. Analysis was conducted using the robust Ward and Peppard method, which incorporates SWOT analysis, Gap analysis, and the McFarlan Strategic Grid. The findings revealed that the company faced significant challenges, including a lack of system integration, limited data analytics capabilities, and suboptimal digital marketing strategies. To address these, the research recommends a cloud-based Enterprise Resource Planning (ERP) system for comprehensive business process integration, a Vendor Management System (VMS) for efficient collaboration, and a Customer Relationship Management (CRM) system for data-driven marketing, with a phased implementation planned for 2026-2028. This comprehensive strategy, underpinned by robust cloud infrastructure and continuous staff training, is poised to not only significantly enhance PT. Songgo Jati Baru's operational efficiency and global market reach but also to solidify its competitive position and ensure sustainable growth in the dynamic trade and services sector.